Estructuración de un plan de cuentas contables dirigido a empresas comerciales conforme la normativa técnica y legal vigente. - Jaramillo Orellana, Gabriela Esthefania (My University, 2022)
Due to globalization, commercial companies nowadays require control over their economic finances and the management of their accounting transactions, providing in such a way that orderly and truthful accounting information is established. In this sense, the chart of accounts is an instrument that allows to carry out a systematic order of the accounting accounts of an entity, which is why this research work focuses on the development of a chart of accounts, through the application of legal and current regulations, in order to improve the processes of accounting records and decision making of businesses in the commercial sector. On the other hand, within the methodology a qualitative approach was established, with a descriptive nature level and the application of the analytical method, concatenated to this, a bibliographic technique will be used since several scientific documents, books and other documents related to the subject of study will be analyzed, which allowed to give as a result a structured chart of accounts for a commercial company where the accounting items for the groups of assets, liabilities, equity, income and expenses are detailed according to the regulatory requirements.
Debido a la globalización las empresas comerciales en la actualidad requieren de un control sobre sus finanzas económicas y el manejo de sus transacciones contables, proporcionando de tal modo que se establezca información contable ordenada y veraz. En tal sentido, el plan de cuentas es un instrumento que permite llevar a cabo un orden sistemático de las cuentas contables de una entidad, es por ello que el presente trabajo de investigación se centra en la elaboración de un plan de cuentas, a través de la aplicación de la normativa legal y vigente, a fin de mejorar los procesos de registro contable y la toma de decisiones de los negocios del sector comercial. Por otro lado, dentro de la metodología se estableció un enfoque cualitativo, con un nivel de naturaleza descriptiva y la aplicación del método analítico, concatenado a esto se hará uso de una técnica bibliográfica ya que se analiza diversos documentos científicos, libros y demás documentos afines a la temática de estudio que permitieron otorgar como resultado un plan de cuentas estructurado para una empresa comercial en donde se detallan las partidas contables para los grupos de activos, pasivos, patrimonio, ingresos y gastos conforme los requerimientos normativos.
Keywords: PLAN DE CUENTAS; SECTOR COMERCIAL; CONTABILIDAD; CONTROL